IDENTIFIKASI KONFLIK PEREBUTAN TANAH ADAT DI DAERAH LAHAN BASAH KABUPATEN BANJAR - Acep Supriadi Wahyu; Mariatul Kiptiah (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2016)
Conflict over customary land dispute in the area of wetlands and located in SouthKalimantan in order of importance of business expansion by certain groups increasingly rife. The results of the research in the first year indicates that the land-related conflicts in wetland areas associated with layered certificate and between the seal and the certificate in the village of Gambut District of Banjar Regency. Generally, conflicts become apparent when peat lands are uncultivated land previously held a high place in the economy due to the access road. High-value economy is usually associated with the interests of residential, business, and other economic interests. The next approach in this research uses a qualitative approach with descriptive methods. The population derived from the conflicts over indigenous land in wetland areas Banjar regency with the sampling technique is purposive sampling. In general, the Focus Group Discussion (FGD) for two events form the basis for formulating a model of conflict resolution of land in wetland areas. Land conflicts that stem from overlapping certificates, certificates and seals both for personal as well as public and indigenous land has led to the completion of both litigation and non litigation. Outcomes of this study is to create a model of conflict resolution of land in wetland areas in Banjar district